2023
DOI: 10.3389/fneur.2023.1132318
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of apparent diffusion coefficient maps in predicting the clinical functional outcomes of acute ischemic stroke

Abstract: PurposeTo investigate texture analysis (TA) based on apparent diffusion coefficient (ADC) map in predicting acute ischemic stroke (AIS) prognosis and discriminating TA features in stroke subtypes.MethodsThis retrospective study included patients with AIS between January 2018 and April 2021. The patients were assigned to the favorable [modified Rankin Scale (mRS) score ≤ 2] and unfavorable (mRS score > 2) outcome groups. All patients underwent stroke subtyping according to the Trial of Org 10,172 in Acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Wang et al ( 9 ) and Zhou et al ( 8 ) used a multivariate logistic regression model to construct an imaging omics nomogram containing patient characteristics and imaging omics characteristics, and the AUC used to predict stroke outcome was greater than 0.80. Sun et al ( 10 ) used clinical features and apparent diffusion coefficient maps to predict poor prognosis of acute stroke (mRS score >2) and the AUC was 0.80. These models were superior to models using non-imaging data, and the clinical data were continuous and related, which demonstrates the great potential of the combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al ( 9 ) and Zhou et al ( 8 ) used a multivariate logistic regression model to construct an imaging omics nomogram containing patient characteristics and imaging omics characteristics, and the AUC used to predict stroke outcome was greater than 0.80. Sun et al ( 10 ) used clinical features and apparent diffusion coefficient maps to predict poor prognosis of acute stroke (mRS score >2) and the AUC was 0.80. These models were superior to models using non-imaging data, and the clinical data were continuous and related, which demonstrates the great potential of the combination.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided diagnosis (CAD) based on MRI has received extensive attention from researchers both domestically and internationally. For example, the texture analysis of apparent diffusion coefficient maps and diffusion-weighted imaging were used to predict the prognosis and subtype of ischemic stroke (8)(9)(10). A systematic review also demonstrated that a combined model combining clinical and imaging variables was more predictive of stroke outcome (11).…”
Section: Introductionmentioning
confidence: 99%